Indonesian SMES and Global Market Penetration: The Effects of Human Capital Investment, Government Role, and Technological Progress - Ali, Ali Mumdin; AM Soma; Ramayuli (Universitas Muhammadiyah Prof. DR HAMKA., 2024)
MSMEs play a significant role in supporting the country's economy as they account for 60.5% of GDP. MSMEs confront a number of difficulties related to financing, supply, and market demand that need to be given more consideration in order to support their entry into the global market. The purpose of this study is to examine how government involvement, technology advancement, human capital investment, and entrepreneurial orientation affect MSMEs (micro, small, and medium-sized firms) in Indonesia and their internationalization strategies. This study uses a quantitative approach with data collection techniques using a Likert scale questionnaire. Then descriptive analysis and Partial Least Squares (PLS) are used to analyze the data. The study's findings show that technical change significantly affects MSMEs' internationalization strategies; in contrast, entrepreneurial orientation, investments in human capital, and the role of the government are not as significant in this regard. However, this research offers stakeholders improved guidance for bolstering MSMEs' success and expansion in global markets, as well as for widening the gap in the global MSME market to promote Indonesia's sustainable economic growth.